Physical activity factsheets for the 28 European union member states of the WHO European region (World Health Organization. Regional Office for Europe, 2018)
The publication focuses on physical activity and health in the countries of the WHO European region. Written for professional public.
Keywords: zdravotní politika; pohybová aktivita; celosvětové zdraví; Evropa; Global Health; Health Policy; Europe; veřejné zdravotnictví; European Union; Motor Activity; Evropská unie; tělovýchovné lékařství